THE IMPACT OF STARTUPS ON ECONOMIC GROWTH IN DEVELOPING COUNTRIES - Rakhimova Shakhnоza Saparbayevna (Ecomind Press, 2025)
This paper examines the growing role of startups in accelerating economic growth in developing countries. Startups, driven by innovation and technological advancement, have emerged as key players in creating jobs, fostering competition, and introducing new products and services into markets. The study explores how startup ecosystems contribute to GDP growth, reduce unemployment, and stimulate private sector development. Particular attention is given to the challenges and opportunities startups face in developing economies, such as limited access to finance, weak infrastructure and regulatory barriers. By analyzing global trends and specific country case studies, this research highlights the importance of government support, foreign direct investment and entrepreneurial education in strengthening startup ecosystems. The paper concludes with practical policy recommendations aimed at enhancing the economic impact of startups in emerging markets.
Keywords: Startups, economic growth, innovation, developing countries, entrepreneurship, startup ecosystem, foreign investment, private sector development, job creation.